2022
DOI: 10.1021/jacs.2c00384
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Reduction Enhances Photodynamic Therapy of Metal–Organic Nanophotosensitizers

Abstract: Herein we report that dimensional reduction from three-dimensional nanoscale metal–organic frameworks (nMOFs) to two-dimensional nanoscale metal–organic layers (nMOLs) increases the frequency of encounters between photosensitizers and oxygen and facilitates the diffusion of singlet oxygen from the nMOL to significantly enhance photodynamic therapy. The nMOFs and nMOLs share the same M12–oxo (M = Zr, Hf) secondary building units and 5,15-di-p-benzoatoporphyrin (DBP) ligands but exhibit three-dimensional and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
(53 reference statements)
0
39
0
Order By: Relevance
“…As porphyrins are extensively studied for photodynamic therapy (PDT) of tumors, the 2D morphological characteristic of nanosheets would benefit the anti-tumor performance of porphyrin-based nanodrugs. 16,25 However, 2D nano-photosensitizers are relatively rare due to the lack of approaches to prepare water-soluble and biocompatible 2D materials. The 2D nanosheets also display a high photosensitizer loading capacity (78.9% by weight, see calculation in the ESI, † section 2) and good stability in cell culture media (see for TEM image of nanosheets), which are ideal properties for nanophotosensitizers.…”
Section: Cytotoxicity and In Vitro Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…As porphyrins are extensively studied for photodynamic therapy (PDT) of tumors, the 2D morphological characteristic of nanosheets would benefit the anti-tumor performance of porphyrin-based nanodrugs. 16,25 However, 2D nano-photosensitizers are relatively rare due to the lack of approaches to prepare water-soluble and biocompatible 2D materials. The 2D nanosheets also display a high photosensitizer loading capacity (78.9% by weight, see calculation in the ESI, † section 2) and good stability in cell culture media (see for TEM image of nanosheets), which are ideal properties for nanophotosensitizers.…”
Section: Cytotoxicity and In Vitro Pdtmentioning
confidence: 99%
“…J-Aggregation is potentially capable of driving porphyrins to assemble into 2-dimensional (2D) nanomaterials, which hold specific advantages in materials science for various applications. 7,16 Due to the strong hydrophobicity and tendency to form H-aggregates, it remains a significant challenge to regulate the stacking of porphyrins to form J-aggregates in water. 17 In our previous studies, adding polyphosphates has been demonstrated as an effective approach to inducing the aggregation of cationic conjugated molecules in water, e.g., H-aggregated porphyrins to assemble nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The active sites in 2D MOLs are completely accessible to organic substrates. 23,24 Furthermore, the capping monocarboxylate modulators in the vertical direction of the SBUs can be modified with active sites via carboxylate exchange to form multifunctional MOLs for catalytic transformations. 25 This strategy has been successfully used to design MOLs for photoredox dual catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent work, a porphyrinic Hf 12 -MOL was successfully synthesized by screening a library of monocarboxylate modulators. 24 Tuning the modulator from acetic acid to propionic acid downsized the product from a 3D MOF to a 2D MOL. Further development of synthetic methods for multifunctional MOLs should allow the design of a new generation of sustainable catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation